Adherence to guideline-directed medical therapy among left ventricular systolic dysfunction patients in Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Manandhar, Reeju; Bogati, Amrit; Prajapati, Dipanker; Aslam, Sheikh; Choudhary, Taanya; Mahat, Sanjeev; Tamrakar, Binita; Neupane, Pushpa; Adhikari, Chandra Mani (Nepalese Heart Journal, 2020)
Background and Aims: Heart Failure (HF) with reduced Ejection Fraction (HFrEF) is defined as the clinical diagnosis of HF and left ventricular ejection fraction (LVEF) ≤ 40%, also referred to as systolic HF. Guideline-directed medical therapy (GDMT) has shown to reduce mortality for HFrEF. We aim to evaluate adherence to GDMT treatment in our outpatients. Methods: It was a cross-sectional observational study. All patients who attended the Department of preventive medicine and cardiac rehabilitation for medical counseling from October 2016 to May 2018 and have already completed 3 months of follow up for HF were included in this study. Performa was designed to collect patient information which included; age, gender, NYHA functional class, LVEF, systolic and diastolic blood pressure, pulse rate, creatinine, potassium and drugs with doses were recorded. Results: Among the 451 patients, ninety-nine (65.6%) were male and 52 (34.4%) were female. The mean age was 56.2±4.2 years. Most of the patients were in NYHA class II 114 (75.5%) and in Sinus rhythm 119 (79.4%). Mean LVEF was 26.6±6.1%. Dilated Cardiomyopathy was the most common clinical diagnosis in 76 (50.3%). Diuretic, Angiotensin-converting enzyme inhibitor (ACEI)/Angitensin receptor blocker (AB), Aldosterone Antagonist, β-blocker and digoxin were prescribed in 151 (100%), 140 (93.3%), 127 (84.1%), 114 (75.4%) and 46 (30.4%) patients respectively. The mean dose of furosemide, Enalapril, Losartan, carvedilol, bisoprolol and metoprolol succinate was 45.3mg, 4.0mg, 33.2mg, 33.6mg, 18.8mg, 3.0mg, and 27.5mg was respectively. Conclusion: Our center’s adherence to GDMT in HFrEF patients is comparable to international studies. We still need more effort to re-emphasize the importance of GDMT by focusing on the optimization of drug doses during out-patient visits.